2013
DOI: 10.1155/2013/743468
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Dynamic Framed-Slotted ALOHA Algorithm Based on Bayesian Estimation and Probability Response

Abstract: This paper proposes an advanced dynamic framed-slotted ALOHA algorithm based on Bayesian estimation and probability response (BE-PDFSA) to improve the performance of radio frequency identification (RFID) system. The Bayesian estimation is introduced to improve the accuracy of the estimation algorithm for lacking a large number of observations in one query. The probability response is used to adjust responsive probability of the unrecognized tags to make the responsive tag number equal to the frame length. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…We define also the system throughput Ut=c1TTrame3.0235ptmonospace[tags/s] as the ratio between the total successful slots and the frame length time . Indeed, the total time to identify all the tags of the system is equal to the total number of frames multiplied by the duration of a frame.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…We define also the system throughput Ut=c1TTrame3.0235ptmonospace[tags/s] as the ratio between the total successful slots and the frame length time . Indeed, the total time to identify all the tags of the system is equal to the total number of frames multiplied by the duration of a frame.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…e minimum distance between the expected value and the actual identification result vector was used to estimate the number of tags [26]. Bayesian estimation and probability response was proposed [13], which can get a relatively accurate statistical result without a large number of observations. Based on the multinomial distribution, the number of empty slots S e was used to estimate the number of tags [27] and the maximum posterior probability distribution (MAP) method was proposed [18], which was defined as follows:…”
Section: Tag Number Estimation At Present Various Methodsmentioning
confidence: 99%
“…To obtain maximum system efficiency, the frame length L i is equal to N i . It can be concluded that the SID wi of F i frame is (13), and the SID ai of F i frame is (14):…”
Section: Frame Length Division Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, frame size L is adjusted according to N at appropriate time instances (e.g., on a frame-by-frame basis) during the identification process. Consequently, the so-called dynamic FSA (DFSA) protocol [6,7,[15][16][17] is more realistic than FSA. However, in this work, we assume that the frame size is fixed throughout the identification process in order to facilitate our discussion, because our interest is focused primarily on the optimal parameter configuration of the FSA protocol for a given N, i.e., we consider the situation after N or N is determined.…”
Section: Introductionmentioning
confidence: 99%